Proceedings IEEE International Symposium on Information Theory,
DOI: 10.1109/isit.2002.1023321
|View full text |Cite
|
Sign up to set email alerts
|

On codes with low peak-to-average power ratio for multi-code CDMA

Abstract: Codes which reduce the peak-to-average power (PAPR) in multi-code code division multiple access (MC-CDMA) communications systems are systematically studied. The problem of designing such codes is reformulated as a new coding-theoretic problem: codes with low PAPR are ones in which the codewords are far from the first-order ReedMuller code. Bounds on the trade-off between rate, PAPR and error-correcting capability of codes for MC-CDMA follow. The connections between the code design problem, bent functions and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In fact, some probabilities can be computed exactly. Paterson has shown that for any word c of length n [18], …”
Section: B Ccdf Of the Paprmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some probabilities can be computed exactly. Paterson has shown that for any word c of length n [18], …”
Section: B Ccdf Of the Paprmentioning
confidence: 99%
“…In [16,17] the impact of an amplifier nonlinearity is investigated for various multicode systems. In [18,19], PAPR reduction codes are systematically studied. Codes which are distant(Hamming sense) from the first-order Reed-Muller code will have small PAPR.…”
Section: Introductionmentioning
confidence: 99%
“…involving not only additive but also multiplicative characters) in relation to many valued sequences [17]. In the second approach, motivated by multi-code CDMA, we are to control the nonlinearity of binary sequences of length a power of 2 [16]. This notion of nonlinearity coincides with the one familiar from boolean functions theory.…”
Section: Introductionmentioning
confidence: 99%
“…In both models sequences live in families and are supposed to form a code either spherical in the first case or binary in the second. Both papers [17,16] already use weighted degree trace codes and our contribution is mostly of extension from Z 4 to Z 2 for > 2 [22], or to non primitive periods [24]. In general, the use of larger rings provides extra flexibility in the design choice; the sequences families constructed in that way having a larger size but a somewhat larger PAPR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation